Analisis Dinamika Penggunaan Lahan Di Area Gumukpasir Parangtritis Kabupaten Bantul Tahun 2003-2014 - Dani, Widya Ayu Elzha, Dr. Kuswaji Dwi Priyono, M.Si, Agus Anggoro Sigit, S.Si, M.Sc (2016)
LANDUSE DYNAMICS ANALYSIS IN SANDDUNES AREA OF PARANGTRITIS BANTUL REGENCY YEAR 2003-2014 Widya Ayu Elzha Dani1, Kuswaji Dwi Priyono2, Agus Anggoro Sigit3 1Student, Faculty of Geography, Universitas Muhammadiyah Surakarta 2,3Lecturers, Faculty of Geography, Universitas Muhammadiyah Surakarta widya.elzha855@gmail.com E100150010 ABSTRACT Sanddunes in Parangtritis is a unique geomorphological appearance, barchan type particularly can be found in tropical area. Barchan is a type of sanddunes with crescent shaped in both tips like a horn which is a natural uniqueness that should be preserved. Landuse dynamics happened in sand dunes area of Parangtritis during a certain period will affecting the development of sanddunes area. Actual data and information towards landuse appearances in sanddunes area in a certain period is needed for monitoring the sanddunes area development as a part of optimization of land resources utilization. The objectives of this study are (1) to knowing the landuse dynamics in sanddunes area of Parangtritis year 2003-2014, (2) to analyze the landuse dynamics in sanddunes area of Parangtritis year 2003-2014. This study used qualitative method and concerned at the satellite imagery data processing, in addition, in-depth interviews conducted to gain more valid and precise data also accountable information. Based on the results that conducted in the conservation area of sanddunes in Parangtritis of 412, 80 hectares. The landuse dynamics map showed the degradation of sand dunes from 216, 11 hectares on 2003 became 37, 98 hectares on 2014 with the sum of degradation area of 178, 13 hectares. The area distribution decreased in the center or core zone of barchan sanddunes because of the unfolded dry land forests. These unfolded dry land forests happened due to the greening programs, settlements, bushes, and shrimp fishponds as the results of local's activities in sanddunes area of Parangtritis. Keywords: dynamics, landuse, sanddunes of Parangtritis